Targets and Timelines for Reducing Salt in Processed Food in the Americas. Issue 9 (31st July 2014) - Campbell, Norm; Legowski, Barbara; Legetic, Branka; Ferrante, Daniel; Nilson, Eduardo; Campbell, Christine; L'Abbé, Mary
<x xml:space="preserve">Abstract</x> Reducing dietary salt is one of the most effective interventions to lessen the burden of premature death and disability. In high‐income countries and those in nutrition transition, processed foods are a significant if not the main source of dietary salt. Reformulating these products to reduce their salt content is recommended as a best buy to prevent chronic diseases across populations. In the Americas, there are targets and timelines for reduced salt content of processed foods in 8 countries—Argentina, Brazil, Canada, Chile, Ecuador, Mexico, and the National Salt Reduction Initiative in the United States and Paraguay. While there are common elements across the countries, there are notable differences in their approaches: 4 countries have exclusively voluntary targets, 2 countries have combined voluntary and regulated components, and 1 country has only regulations. The countries have set different types of targets and in some cases combined them: averages, sales‐weighted averages, upper limits, and percentage reductions. The foods to which the targets apply vary from single categories to comprehensive categories accounting for all processed products. The most accessible and transparent targets are upper limits per food category. Most likely to have a substantive and sustained impact on salt intake across whole populations is the combination of sales‐weighted averages and upper limits. To assist all countries with policies to improve the overall nutritional value of processed foods, the authors call for food companies to supply food composition data and product sales volume data to transparent and open‐access platforms and for global companies to supply the products that meet the strictest targets to all markets. Countries participating in common markets at the subregional level can consider harmonizing targets, nutrition labels, and warning labels.